The Difference in Effectiveness of Mung Bean Drink and Red Guava Juice on Hemoglobin Level Increase - Amirul Amalia; Nahardian Vica R; Dias Tiara Putri Utomo (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
Iron deficiency anemia is the biggest health problem in the world, especially for young women. The prevalence of anemia in adolescents is 27% in developing countries and 6% in developed countries. In Indonesia, the prevalence of anemia is quite high, namely 21.7% with a proportion of 22.8% in rural areas and 20.6% in urban areas and 23.9% in women and 18.4% in men. This study aimed to determine the difference in the effectiveness of mung bean drink and red guava juice on increasing Hb level. This research applied a Quasy-Experimental research design. The research sample consisted of 90 female students who were divided into 2 groups. Before giving the intervention, a pre-test was carried out by measuring the Hb level, and then the samples were given treatment for 7 days and Post-test on the last day. The results showed that mung bean drink affected hemoglobin increase with a value of p = 0.000 and guava juice also affected hemoglobin increase with a value of p = 0.004. There was a difference in giving mung bean drink with red guava juice on the increase in Hb levels with a value of p = 0.045. It is expected that the results of this study could provide additional information regarding the difference in the effectiveness of giving mung bean drink and guava juice on increasing Hb levels and providing input for clinicians to manage anemia, especially in adolescent girls.